A Comparison of Different Modes of Morning Priming Exercise on Afternoon Performance - Richard Bracken (International Journal of Sports Physiology and Performance, 2016)
Purpose:To assess the effects of different modes of morning (AM) exercise on afternoon (PM) performance and salivary hormone responses in professional rugby union players.Methods:On 4 occasions (randomized, crossover design), 15 professional rugby players provided AM (~8 AM) and PM (~2 PM) saliva samples before PM assessments of countermovement-jump height, reaction time, and repeated-sprint ability. Control (passive rest), weights (bench press: 5 × 10 repetitions, 75% 1-repetition maximum, 90-s intraset recovery), cycling (6 × 6-s maximal sprint cycling, 7.5% body mass load, 54-s intraset recovery), and running (6 × 40-m maximal sprints, 20-s intraset recovery) interventions preceded (~5 h) PM testing.Results:PM sprint performance improved (P < .05) after weights (>0.15 ± 0.19 s, >2.04% ± 2.46%) and running (>0.15 ± 0.17 s, >2.12% ± 2.22%) but not cycling (P > .05). PM jump height increased after cycling (0.012 ± 0.009 m, 2.31% ± 1.76%, P < .001) and running (0.020 ± 0.009 m, 3.90% ± 1.79%, P < .001) but not weights (P = .936). Reaction time remained unchanged between trials (P = .379). Relative to control (131 ± 21 pg/mL), PM testosterone was greater in weights (21 ± 23 pg/mL, 17% ± 18%, P = .002) and running (28 ± 26 pg/mL, 22% ± 20%, P = .001) but not cycling (P = .072). Salivary cortisol was unaffected by AM exercise (P = .540).Conclusions:All modes of AM exercise improved at least 1 marker of PM performance, but running appeared the most beneficial to professional rugby union players. A rationale therefore exists for preceding PM competition with AM exercise.